Reciprocal Teaching as a Technique To Promote Students’ Critical Thinking in Comprehending a Text for Senior High School Students (RETAIN, 2020)
The students’ interest in learning and reading English text is very low. It is because many of them think that English as a foreign laguage in Indonesia so they don’t need to comprehend it deeply. On the other hand, based on 2013 curriculum students are expected to become independent and critical learners in the learning process. Thus, the role of the teacher in selecting the teaching technique is important in order to make the students interesting in comprehending an English text. Moreover, teaching and learning in group discussion can be more effective because the students can respectively state their toughts. The group discussion which is called as reciprocal teaching is carried out through several stages such as predicting, questioning, clarifying, and concluding. This technique encourages the students to think critically and comprehend the narrative text deeply. The subjects of the study were tenth grader high school students in Gresik. The Researcher conducts the observations, records the implementation of technique, and observes the student worksheets. It aims to describe the use of technique and the way of students critically thinking. The results showed that the teacher used the suitable stages based on several research theories and this technique was able to encourage that students become critical thinker through some stages and answering some of high order thinking skills questions.